Condiciones turísticas del caserío de huashgon provincia de santiago de chuco para desarrollar el turismo rural comunitario - Lujan Castillo, Saira Maritza (2015)
This paper called: CONDITIONS TOURIST OF THE VILLAGE OF HUASHGON PROVtNCE OF SANTIAGO DE CHUCO TO DEVELOP TOURtSM RURAL COMMUNITY, has been produced in the geographical setting and cultural village of Huashgón, taking as central to folklore including gastronomy as is the ajiaco dish prepared with guinea pig own inputs in the area; traditional customs such as the Minga is very traditional in the village, also talked about agricultura! Activities using traditional techniques such as planting in this technique the y.oke of bulls is used, the plow and the yoke, the other in this technique tirapar activity villagers pull the weeds of crops to grow well, the technique of harvesting crops there for family consumption is harvested. Found in the village of Huashgón palio dance as the original dance and danced in place any cultural event held nationwide dance today is cultural heritage of the nation also recorded the traditional festival in honor of Lord Merey held in September each year. To obtain information methods were used: Ethnographic, Analytic – Synthetic and Systematic well as techniques such as direct observation participant survey and signing; and finally the instruments used were the chips, the questionnaire survey, field notebook, camera and camcorder